Construction site on Christmas night - Rinker, Sherri Duskey; Ford, AG (San Francisco, California : Chronicle Books LLC, 2018)
It is Christmas Eve, and all the construction vehicles are finishing up work on the site, and when they leave they find that there is a special present waiting for each of them.
AD590L
Decoding demand: 53 (medium) Semantic demand: 87 (very high) Syntactic demand: 84 (very high) Structure demand: 85 (very high)
Keywords: Construction equipment -- Juvenile fiction; Gifts -- Juvenile fiction; Stories in rhyme; Christmas fiction; Picture books